Role of oxidative stress in ERK and p38 MAPK activation induced by the chemical sensitizer DNFB in a fetal skin dendritic cell line - Matos, MT (2010)
The intracellular mechanisms involved in the early phase of dendritic cell (DC) activation upon contact with chemical sensitizers are not well known. The strong skin sensitizer 2,4-dinitrofluorobenzene (DNFB) was shown to induce the activation of mitogen-activated protein kinases (MAPK) in DC. In the present study, we investigated a putative role for oxidative stress in DNFB-induced MAPK activation and upregulation of the costimulatory molecule CD40. In a DC line generated from fetal mouse skin, DNFB induced a significant increase in protein oxidation, measured by the formation of carbonyl groups, while it had almost no effect on lipid peroxidation. The antioxidants glutathione and vitamin E, which inhibit protein and lipid oxidation, respectively, were used to assess the role of oxidative stress in DNFB-induced MAPK activation. Glutathione, but not vitamin E, inhibited DNFB-induced p38 MAPK and ERK1/2 phosphorylation, whereas none of the antioxidants interfered significantly with the DNFB-induced upregulation of CD40 protein levels. Taken together, these results indicate that DNFB activates p38 MAPK and ERK1/2 via production of reactive oxygen species, and that protein oxidation plays an important role in MAPK activation.